Development of smart samplers and their comparison to dried serum spots for the analysis of growth hormone releasing hormone analogs using LCHRMS/MS - Christina Johannsen; Anna Kha Tu Nguyen; Sasha Shabani; Inger Oulie; Siri Dørum; Yvette Dehnes; Leon Reubsaet; Trine Grønhaug Halvorsen (Advances in Sample Preparation)
Growth hormone-releasing hormone (GHRH) analogs, including sermorelin, CJC-1295, and tesamorelin, are prohibited in sports due to their performance-enhancing potential. Detecting these peptides remains challenging, requiring sensitive analytical techniques. This study explores the feasibility of dried serum spots (DSS) and smart samplers for detecting GHRH analogs in human serum using liquid chromatography-high-resolution tandem mass spectrometry. Smart samplers combine sampling and sample preparation in one tool; in this study smart samplers were developed using divinyl sulfone functionalized paper to immobilize antibodies for selective analyte capture. DSS and smart samplers were compared for extraction efficiency, precision, and detection capabilities. Various extraction approaches were evaluated to optimize analyte recovery followed by a blind sample study to assess detection capability at unknown concentrations. Results showed that DSS yielded higher overall signal intensities but exhibited greater variability. In contrast, smart samplers demonstrated improved reproducibility and sensitivity at lower concentrations. Smart samplers successfully identified sermorelin at 0.25 ng∙mL-1, CJC-1295 at 4 ng∙mL-1, and tesamorelin at 2.5 ng∙mL-1, while DSS exhibited limitations at these concentrations. This study presents a proof-of-concept for using smart samplers and DSS in anti-doping analysis. While the results shown are promising, further optimization is needed to improve analyte recovery and sampler stability. The findings support the potential of alternative blood sampling techniques in doping control and peptide biomarker analysis.